PENGHAPUSAN PRESIDENTIAL THRESHOLD SEBAGAI UPAYA PEMULIHAN HAK-HAK KONSTITUTIONAL - Armia, Muhammad Siddiq (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
The removal of the presidential threshold system, on the one hand, has made a positive impact on the development of democracy in Indonesia. It can restore the basic rights of the citizens in the constitution (remedy of constitutional rights) that had been hurt by the threshold. The advantages include the minor parties’ opportunity to propose their respective presidential candidates and also the prospect of having more diversed presidential candidates. The new system will allow the president to be at ease in carrying out the governmental duties due to the absence of the dominant parties’ intervention in the parliament. However, the weaknesses of the abolition of the presidential threshold should also be of concern because of the vulnerability of individual interests that may be obtained through the presidential nomination. In terms of the national security, there will be an expansion of conflict and criminal acts escalation attributed to the candidates' election. Further, for the efficiency itself, the electoral budget allocation will greatly increase (high cost election). This will nevertheless an issue because such excessive budget allocation may be better supplied to areas that can increase the people’s welfare. Therefore, this assumption needs to be investigated further with in-depth research on the efficiency of campaign funds.